Identification of Herpesvirus Proteins That Contribute to G(1)/S Arrest - Paladino, Patrick (American Society for Microbiology, 2014)
Lytic infection by herpesviruses induces cell cycle arrest at the G(1)/S transition. This appears to be a function of multiple herpesvirus proteins, but only a minority of herpesvirus proteins have been examined for cell cycle effects. To gain a more comprehensive understanding of the viral proteins that contribute to G(1)/S arrest, we screened a library of over 200 proteins from herpes simplex virus type 1, human cytomegalovirus, and Epstein-Barr virus (EBV) for effects on the G(1)/S interface, using HeLa fluorescent, ubiquitination-based cell cycle indicator (Fucci) cells in which G(1)/S can be detected colorimetrically. Proteins from each virus were identified that induce accumulation of G(1)/S cells, predominantly tegument, early, and capsid proteins. The identification of several capsid proteins in this screen suggests that incoming viral capsids may function to modulate cellular processes. The cell cycle effects of selected EBV proteins were further verified and examined for effects on p53 and p21 as regulators of the G(1)/S transition. Two EBV replication proteins (BORF2 and BMRF1) were found to induce p53 but not p21, while a previously uncharacterized tegument protein (BGLF2) was found to induce p21 protein levels in a p53-independent manner. Proteomic analyses of BGLF2-interacting proteins identified interactions with the NIMA-related protein kinase (NEK9) and GEM-interacting protein (GMIP). Silencing of either NEK9 or GMIP induced p21 without affecting p53 and abrogated the ability of BGLF2 to further induce p21. Collectively, these results suggest multiple viral proteins contribute to G(1)/S arrest, including BGLF2, which induces p21 levels likely by interfering with the functions of NEK9 and GMIP. IMPORTANCE Most people are infected with multiple herpesviruses, whose proteins alter the infected cells in several ways. During lytic infection, the viral proteins block cell proliferation just before the cellular DNA replicates. We used a novel screening method to identify proteins from three different herpesviruses that contribute to this block. Several of the proteins we identified had previously unknown functions or were structural components of the virion. Subsets of these proteins from Epstein-Barr virus were studied for their effects on the cell cycle regulatory proteins p53 and p21, thereby identifying two proteins that induce p53 and one that induces p21 (BGLF2). We identified interactions of BGLF2 with two human proteins, both of which regulate p21, suggesting that BGLF2 induces p21 by interfering with the functions of these two host proteins. Our study indicates that multiple herpesvirus proteins contribute to the cell proliferation block, including components of the incoming virions.